2013
DOI: 10.1631/jzus.b1200185
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sensitization to weed pollens of Humulus scandens, Artemisia vulgaris, and Ambrosia artemisiifolia in northern China

Abstract: The intradermal prevalence of weed pollen sensitization among allergic subjects in northern China is about 13.5%. Correlations of specific IgE antibodies suggest that pollen allergens from Artemisia and Humulus are independent sources for primary sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…There was a markedly higher frequency of specific IgE to Artemisia (58.3%) correlating to Art v 1 reactivity (49%). In contrast, specific IgE to Ambrosia (14.7%) and Amb a 1 (11.2%) was lower in frequency and level, not correlated with each other, and uncommon in the absence of specific IgE to Art v 1 suggesting primary sensitization with Artemisia species . Epidemiological studies on pollen‐allergic patients performed in Spain identified a frequency of sensitization to Art v 1 of 13% .…”
Section: Sensitization To Individual Molecules and Their Clinical Relmentioning
confidence: 89%
“…There was a markedly higher frequency of specific IgE to Artemisia (58.3%) correlating to Art v 1 reactivity (49%). In contrast, specific IgE to Ambrosia (14.7%) and Amb a 1 (11.2%) was lower in frequency and level, not correlated with each other, and uncommon in the absence of specific IgE to Art v 1 suggesting primary sensitization with Artemisia species . Epidemiological studies on pollen‐allergic patients performed in Spain identified a frequency of sensitization to Art v 1 of 13% .…”
Section: Sensitization To Individual Molecules and Their Clinical Relmentioning
confidence: 89%
“…A total of 1,144 subjects (aged from 5 to 68) from June to October 2011 underwent intradermal testing using a panel of 25 allergen sources [ 65 ]. Of the 1,144 subjects, 170 had positive intradermal reactions to pollen and 144 donated serum for IgE testing from these 170 subjects.…”
Section: Epidemiology Of Artemisia Allergymentioning
confidence: 99%
“…Component‐resolved diagnosis (CRD) enables IgE sensitization profiles and potential risk to be established, and whether specific IgE is the result of primary sensitization or cross‐reactivity can also be determined . Such information can assist in making the right choice of immunotherapy, particularly when pollen seasons of different allergenic sources overlap . Seven Artemisia pollen allergens have been identified and listed in the IUIS database (http://www.allergen.org), including the recently added 62 kDa putative galactose oxidase protein (Art an 7), first purified from sweet wormwood ( A. annua ) .…”
Section: Introductionmentioning
confidence: 99%